2019
DOI: 10.7759/cureus.4547
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Length of Stay for Observation Patients

Abstract: Objectives The objective of this study was to determine whether the addition of a case manager and a physician advisor to the observation unit would decrease the length of stay (LOS) of observation patients. Study design This retrospective, observational study for observation patients was conducted in 2017. Methods At a tertiary-care, medium-sized, urban, community hospital, the LOS for all observation patients in 2017 (2, 981 clinical decision unit [CDU] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…( 24 ) This study showed that sex is not a predictor of prolonged LOS. This is similar to Mohamed Mosaad ( 25 ), and Dada and Sule ( 26 ) studies. The present study also shows that non-Saudi patients were more likely to experience a prolonged LOS, this is likely due to administrative reasons, as many of these patients require eligibility reviews according to their insurance categories.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…( 24 ) This study showed that sex is not a predictor of prolonged LOS. This is similar to Mohamed Mosaad ( 25 ), and Dada and Sule ( 26 ) studies. The present study also shows that non-Saudi patients were more likely to experience a prolonged LOS, this is likely due to administrative reasons, as many of these patients require eligibility reviews according to their insurance categories.…”
Section: Discussionsupporting
confidence: 90%
“…This is likely due to the high-prevalence of chronic hematological conditions such as Sickle-cell disease in the Eastern Province of Saudi Arabia which frequently presents to hospital with vaso-occlussive crises requiring hydration & analgesia or fever requiring blood investigations and septic workup. Similarly, a study by Gravel et al found that chronic complex conditions, such as congenital heart disease or cystic fibrosis, had longer LOS in PEDs compared to patients without these conditions ( 30 ) In contrast, several studies have found that respiratory-related complaints were the most common predictive factor for prolonged LOS ( 24 - 26 , 31 ). In the present study, the most common presenting complaint among the prolonged LOS patients were related to respiratory complaints but did not result in a statistically significant increase of their LOS compared to other conditions in the prolonged LOS group.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, when considering patient volume from 2020 to 2022, our study projected potential cost savings of USD 3116, 8212.50 over three years. These findings align with Dada and Aule's study, which identified factors influencing LOS for observation patients [19]. Our work complements their findings by offering a tangible financial perspective, elucidation how even modest reductions in LOS can yield substantial cost savings and resource optimization.…”
Section: Discussionsupporting
confidence: 89%
“…Observational evidence has been published demonstrating the positive impact of observation units on length of stay. [19] Establishing a dedicated observation unit and the standard work associated with its operation is one of the keys to a favorable observation length of stay in the WellSpan Summit Health system. Daily interdisciplinary rounds created a process for sharing UM knowledge to improve the accuracy and efficiency of the level of care determination process.…”
Section: Discussionmentioning
confidence: 99%